Menelaah Rasionalitas Petani Perkembunan Tanaman Tua Menggunakan Gagasan James S. Coleman - Wurianti, Lisa; Anggreta, Dian Kurnia; Yuhelna, Yuhelna (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2024)
This study examines the rationality of Plantation Farmers (Palm Oil) in facing market price fluctuations (selling prices of plantation products). Palm oil is subject to price dependency on the global level, resulting in price fluctuations of Fresh Fruit Bunches (FFB) that are felt by farmers at the local level. This condition places farmers in a vulnerable position when the selling price of their plantation products decreases. Although farmers do not have control over the fluctuation in the selling prices of their agricultural products, the decisions they make in dealing with these fluctuations are interesting to examine. This study employs the Rationality theory of James S. Coleman. The qualitative approach, using a single case study research design, is employed to examine the decisions made by the farmers. The data collection process involves conducting in-depth interviews with palm oil farmers, plantation product buyers, and local government officials; non-participant observation to directly observe plantation product transactions and palm oil farmers' activities; and document analysis. The research findings indicate that farmers choose to engage in several activities like as purchasing land, buying jewelry made of gold, and saving cash when the price of FFB (crude palm oil) is high. Meanwhile, when the price of FFB drops, farmers choose to: minimize daily expenses, apply for a loan to palntation product buyers and banks. The theory of Coleman can assist this research in elucidating the deliberate actions taken by farmers in utilizing their resources and potential. The decision was carefully considered, taking into account the existing structure and culture within the local community.Penelitian ini membahas rasionalitas Petani Perkembunan Tanaman Tua (Kelapa Sawit) dalam menghadapi fluktuasi harga pasar (harga jual hasil perkebunan). Kelapa sawit memiliki ketergantungan harga pada tingkat global, menyebabkan fluktuasi harga Tandan Buah Segar (TBS), dirasakan oleh petani di tingkat lokal. Kondisi ini memposisikan petani berada dalam kerentanan saat harga jual produk pekebunan tersebut turun. Meskipun petani tidak memiliki kontrol atas fluktuasi harga jual produk perkebunan mereka, namun keputusan yang mereka ambil dalam menghadapi fluktuasi menjadi menarik untuk ditelaah. Penelitian ini menggunakan teori Rasionalitas James S. Coleman. Pendekatan kualitatif, dengan tipe penelitian studi kasus tunggal, digunakan untuk menelaah keputusan para petani tersebut. Proses pengumpulan data dilakukan dengan: wawancana mendalam pada petani kelapa sawit, pemilik peron (pembeli produk perkebunan dari petani), dan pemerintah lokal; observasi non partisipan dilakukan untuk melihat langsung aktivitas transaksi jual beli produk perkebunan, aktivitas petani kelapa sawit; dan studi dokumen. Hasil penelitian menunjukkan bahwa Petani memilih melakukan beberapa hal seperti: membeli tanah, membeli perhiasan, dan menyimpan uang tunai, saat harga TBS tinggi. Sedangkan pada saat harga TBS turun, para petani memilih untuk: meminimalisir pengeluaran, meminjam keperon kelapa sawit, dan Bank. Gagasan Coleman dapat membatu penelitian ini untuk menjelaskan tindakan yang diambil oleh petani dipilih secara sadar dengan memanfaatkan sumber daya, dan potensi yang dimiliki oleh petani tersebut. Pilihan tersebut dipertimbangkan dengan matang, juga mendapat pengaruh struktur dan kultur yang ada dalam masyarakat setempat.